2020
DOI: 10.1021/acsomega.0c00855
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Power Conversion Efficiency of Quantum Dot-Sensitized Solar Cells by Doping of Manganese into a ZnS Passivation Layer and Cosensitization of Zinc-Porphyrin on a Modified Graphene Oxide/Nitrogen-Doped TiO2 Photoanode

Abstract: It is vital to acquire power conversion efficiencies comparable to other emerging solar cell technologies by making quantum dot-sensitized solar cells (QDSSCs) competitive. In this study, the effect of graphene oxide (GO), nitrogen, manganese, and a porphyrin compound on the performance of QDSSCs based on a TiO2/CdS/ZnS photoanode was investigated. First, adding GO and nitrogen into TiO2 has a conspicuous impact on the cell efficacy. Both these materials reduce the recombination rate and expand the specific su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…According to Akman’s [ 40 ] research, doping the Mn/ZnO photoanode in solar cell applications resulted in stability and an improvement in efficiency of 2.11–4.20% for 3.34-3.19 eV. Fadaam et al [ 41 ] demonstrated enhanced conversion for MnS through annealing at 300 °C with a band-gap energy of 2.9 eV. Cao et al [ 42 ] reported on the heterojunction structure of NiS2/MnS with 6.44 % and 4.81% for MnS FTO as a potential counter electrode to replace Pt as a low-cost and highly efficient material for dye-sensitized solar cells.…”
Section: Resultsmentioning
confidence: 99%
“…According to Akman’s [ 40 ] research, doping the Mn/ZnO photoanode in solar cell applications resulted in stability and an improvement in efficiency of 2.11–4.20% for 3.34-3.19 eV. Fadaam et al [ 41 ] demonstrated enhanced conversion for MnS through annealing at 300 °C with a band-gap energy of 2.9 eV. Cao et al [ 42 ] reported on the heterojunction structure of NiS2/MnS with 6.44 % and 4.81% for MnS FTO as a potential counter electrode to replace Pt as a low-cost and highly efficient material for dye-sensitized solar cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, several other concepts upgrading the PA/QDs passivation methods reported will be discussed in detail. 110–113…”
Section: Defects At the Photoanode/electrolyte Interface And The Impo...mentioning
confidence: 99%
“…MoS2 exhibited the lowest PCE; this was due to the nanoparticles having a higher charge transfer resistance, which resulted in Power conversion efficiency for the developed solar cells increased in the following order: MoS 2 (6.05%) < MoTe 2 (6.93%) < MoSe 2 (7.05%). MoS 2 exhibited the lowest PCE; this was due to the nanoparticles having a higher charge transfer resistance, which resulted in the limitation of electron transfer, subsequently resulting in low electron-hole recombination, hence, in limited efficiency [22]. Low efficiency might be due to the increased surface area and thickness on the photoanode which results in charge transfer resistance [23,24].…”
Section: Current-voltage and Photovoltaic Measurementsmentioning
confidence: 99%